ANALYSIS OF SUPPLY CHAIN MANAGEMENT OF SQUID SEA FISH IN TRADITIONAL FISHERMAN IN VILLAGE OF FISHERMAN INDAH MEDAN - Umar Hamdan Nasution; Syamsurizal Syamsurizal; Cut Zahri (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
This study states that the implementation of the squid sea fish supply chain in the Nelayan Indah Village, Medan Labuhan District, Medan City, is still controlled by collectors, the demand for squid fish in the Nelayan Indah Village, Medan Labuhan District, Medan City is still very high and the supply of fish squid sea depends on the harvest season, weather, techniques and technology used in fishing vessels, and pricing of squid fish in the Nelayan Indah Village Medan Labuhan District Medan City based on the demand and supply.